2010
DOI: 10.1103/physreva.81.033835
|View full text |Cite
|
Sign up to set email alerts
|

Soliton-guided phase shifter and beam splitter

Abstract: We propose, analyze, and study numerically a phase shifter for light wave packets trapped by Kerr solitons in a nonlinear medium. We also study numerically a previously proposed soliton-guided nonpolarizing beam splitter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The induced-phase-modulation (or cross-phase-modulation) process has been predicted two decades ago [1,2,9,10], and experimentally observed [3,4] to occur when a lowpower signal (either an harmonic cw signal or a weakly nonlinear signal) couples to a high-intensity pump signal, the later one providing an optical waveguiding structure and reshaping channel to the first for substantial increase of its lifetime. However while this process is rather well understood for single-soliton pumps and in the case of relatively weak cross-phase-modulation processes, almost no insight exists about the context of pump signals consisting of periodic networks of temporal or spatial solitons [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The induced-phase-modulation (or cross-phase-modulation) process has been predicted two decades ago [1,2,9,10], and experimentally observed [3,4] to occur when a lowpower signal (either an harmonic cw signal or a weakly nonlinear signal) couples to a high-intensity pump signal, the later one providing an optical waveguiding structure and reshaping channel to the first for substantial increase of its lifetime. However while this process is rather well understood for single-soliton pumps and in the case of relatively weak cross-phase-modulation processes, almost no insight exists about the context of pump signals consisting of periodic networks of temporal or spatial solitons [18].…”
Section: Resultsmentioning
confidence: 99%
“…Since this key input as well as the subsequent experimental evidences reported in [3,4] it has become evident that besides their most common applications in long-distance transmission of high-power signals [5,6], solitons could be prime candidates for controlling light by light [7,8]. More advanced studies have been carried out in recent years based on numerical simulations, and revealed that due to their unique stability properties solitons provide excellent and reliable guiding structures for reconfigurable low-power signals and re-routinable high-power pulses [9,10]. Particularly attracting is the possibility to construct soliton networks that can be used as nonlinear waveguide arrays, as established in the landscape of recent experiments [11,12,13,14,15,16] emphasizing the outstanding robustness of the periodic lattices of optical solitons with flexible (hence controllable) refractive index modulation depth and period that are induced all-optically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proven in the seminal paper by Knill et al that it is possible to implement general quantum computing using only beam-splitters, phase-shifters, single-photon sources and photo-detectors [10]. In a series of papers [21][22][23], Steiglitz has demonstrated that the scheme proposed by Knill et al scheme can be realized using soliton-guided photons.…”
Section: Introductionmentioning
confidence: 99%
“…Optical solitons can maintain their shapes and velocities during their propagation under the balance between group-velocity dispersion (GVD) and Kerr nonlinearity 4 . By virtue of the advantage of shape preserving, optical solitons have been applied in the optical switching, phase shifter, amplifier, and information storage 5 6 7 8 .…”
mentioning
confidence: 99%